2020
DOI: 10.1021/acsami.0c02124
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Cobalt/Amorphous LaCoOx Hybrid Nanoparticles Embedded in Porous Nitrogen-Doped Carbon as Efficient Electrocatalysts for Hydrazine-Assisted Hydrogen Production

Abstract: Hydrazine electro-oxidation has received substantial attention owing to its high energy density, low onset potential, and wide applications in hydrazine-assisted hydrogen production and direct hydrazine fuel cells. In this work, crystalline cobalt/ amorphous LaCoO x hybrid nanoparticles embedded in porous nitrogen-doped carbon (N-C) were fabricated via pyrolytic decomposition of the dual-metal lanthanum-incorporated zeolitic imidazolate framework (La/ZIF-67), which exhibit high activity and stability toward th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…Besides, the peaks at 532.0 and 532.8 eV correspond to the adsorbed water and the oxygen atoms bonding with carbon. [ 72 ] Interestingly, a weak peak at 535.5 eV originated from the surface peroxide species can be identified for the catalysts after stability tests, which is consistent with previous reports on Co‐based OER catalysts after long‐term operation. [ 40,66 ] Overall, the pre‐oxidation process plays an important role in facilitating the OER catalysis, and the small particle size, facile charge transfer behavior and favorable Co 2+ ‐to‐Co 3+ conversion of the CoCo PBA pre‐catalyst could lead to remarkable accumulation of the catalytically active species.…”
Section: Resultssupporting
confidence: 89%
“…Besides, the peaks at 532.0 and 532.8 eV correspond to the adsorbed water and the oxygen atoms bonding with carbon. [ 72 ] Interestingly, a weak peak at 535.5 eV originated from the surface peroxide species can be identified for the catalysts after stability tests, which is consistent with previous reports on Co‐based OER catalysts after long‐term operation. [ 40,66 ] Overall, the pre‐oxidation process plays an important role in facilitating the OER catalysis, and the small particle size, facile charge transfer behavior and favorable Co 2+ ‐to‐Co 3+ conversion of the CoCo PBA pre‐catalyst could lead to remarkable accumulation of the catalytically active species.…”
Section: Resultssupporting
confidence: 89%
“…In addition, constructing amorphous nanostructures with beneficial chemical compositions that have a high tendency for pre-oxidation could further promote the in situ generation of the high-valence active species during the anodic processes. 13,14 For example, the Cao group reported an amorphous nickel sulfoselenide catalyst grown on nickel foam, which displays high activity towards UOR and HER catalysis. 66 Detailed analyses indicated that the as-prepared amorphous Ni-S-Se pre-catalyst could be rapidly transformed into the NiOOH phase, which is the real active species for the UOR.…”
Section: Modulation Of the Crystallinitymentioning
confidence: 99%
“…Electrocatalytic energy conversion pathways have received substantial research interest owing to their multiple merits including high energy conversion efficiency, satisfactory reaction selectivity and environmental friendliness. [1][2][3][4][5] For example, fuel cells coupled by the oxygen reduction reaction (ORR) and the electro-oxidation reactions of energy-containing small molecules, such as hydrogen, 6,7 urea, [8][9][10][11] hydrazine, [12][13][14][15] as well as lower alcohols, [16][17][18][19] could efficiently convert the chemical energy to electricity. In another pathway, the electrode coupling between the cathodic hydrogen evolution reaction (HER) and anodic oxygen evolution reaction (OER) could lead to efficient production of clean hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…The development of simple bi‐metallic or bi‐metallic core‐shell nanostructures is of great interest due to its distinct properties (cooperative activity or optimal binding strength), which is not accessible in common conventional monometallic‐type catalysts system, is considered as new class of active catalysts in hydrazine fuel cell applications [40–46] . In particular, the progress on development of alternative bi‐metallic or bi‐metallic core‐shell nanostructures has received much attention in this area of research.…”
Section: Introductionmentioning
confidence: 99%